Hubungan Kecemasan Ibu Hamil Trimester III Selama Masa Pandemi Covid-19 terhadap Cakupan Pemeriksaan Kehamilan di Kelurahan Kertosari Kabupaten Banyuwangi - Miftahul Hakiki; Nurul Eko Widiyastuti; Setiana Andarwulan (EMBRIO: Jurnal Kebidanan, 2022)
Pregnancy is a natural process. Changes that occur in women during normal pregnancy are physiological, the care provided by minimize intervention. The impact of the Covid-19 pandemic on pregnant women is the emergence of a concern/anxiety related to neonatal growth and development. Therefore, pregnant women need special attention regarding prevention, diagnosis, and management. Anxiety is a state of understanding or worrying that something bad will happen. According to WHO policy, the standard of care for pregnancy is at least 4 visits, one time visit in the 1st trimester, one time visit in the 2nd trimester, two time visit in the 3nd trimester. The study aims to identify the anxiety of pregnant women during the Covid-19 pandemic, to identify the coverage of antenatal care and to analyze the relationship between the anxiety of third trimester pregnant women during the Covid-19 pandemic and the coverage of antenatal care.Cross sectional research design. The population is all third trimester pregnant women in Kertosari Village. The sample taken is 35 respondents, using purposive sampling technique. Collecting data using questions for the anxiety of pregnant women and coverage of antenatal care. Data analysis using Chi Square test with significant results 0.005 where significant 0.005 > 0.05. It was concluded that there was a positive correlation between the anxiety of pregnant women in the third trimester of coverage of antenatal care during the Covid-19 pandemic. So it can be said that the high anxiety of pregnant women in the third trimester will cause low antenatal care visits.